1999
DOI: 10.1006/viro.1999.9902
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of APSE-1, a Bacteriophage Infecting the Secondary Endosymbiont of Acyrthosiphon pisum

Abstract: A bacteriophage infecting the secondary endosymbiont of the pea aphid Acyrthosiphon pisum was isolated and characterized. The phage was tentatively named bacteriophage APSE-1, for bacteriophage 1 of the A. pisum secondary endosymbiont. The APSE-1 phage particles morphologically resembled those of species of the Podoviridae. The complete nucleotide sequence of the bacteriophage APSE-1 genome was elucidated, and its genomic organization was deduced. The genome consists of a circularly permuted and terminally red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 21 publications
3
87
0
2
Order By: Relevance
“…PCR primers were designed to detect close homologs of several regions of the APSE genome, including conserved regions common to all isolates, as well as the stx homolog from APSE-1 (P7 in ref. 7) and the cdtB sequences present in our assemblies. Primers for phage genes were APSEP2F1 and APSEP2R1, APSE3.9F and APSE8.1R (all listed above), and APSE3.6F (5Ј-GGA GCA AAA AAA CAT GAG CAG-3Ј) and APSE4.2R (5Ј-CTC CGG GTC CAT GTC TAA TCG-3Ј).…”
Section: Distribution Of Phage Genes In Different Isolates Of H Defementioning
confidence: 99%
See 2 more Smart Citations
“…PCR primers were designed to detect close homologs of several regions of the APSE genome, including conserved regions common to all isolates, as well as the stx homolog from APSE-1 (P7 in ref. 7) and the cdtB sequences present in our assemblies. Primers for phage genes were APSEP2F1 and APSEP2R1, APSE3.9F and APSE8.1R (all listed above), and APSE3.6F (5Ј-GGA GCA AAA AAA CAT GAG CAG-3Ј) and APSE4.2R (5Ј-CTC CGG GTC CAT GTC TAA TCG-3Ј).…”
Section: Distribution Of Phage Genes In Different Isolates Of H Defementioning
confidence: 99%
“…Microscopy has revealed that H. defensa can live within the bacteriocytes that normally house Buchnera, within some other cell types, and extracellularly in the insect hemocoel (1,2). In a European pea aphid strain, secondary symbionts were found to harbor an active bacteriophage, designated APSE-1; its genome sequence indicated a relationship to P22, the lambdoid phage of Salmonella enterica (7,8). The secondary symbiont serving as host to APSE-1 was not identified initially, but, based on a survey of aphid species harboring different symbionts (2), APSE-1-like phage appear to be consistently and exclusively associated with H. defensa.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further sequence database searches with BLASTP+BEAUTY revealed that the protein encoded by ORF178 had significant homology with the lysozymes of Haemophilus influenzae phage HP1 (53 % similarity, 36 % identity; Benjamin et al, 1984;Esposito et al, 1996), E. coli phage P1 (51 % similarity, 33 % identity; Schmidt et al, 1996), APSE-1, a bacteriophage from an endosymbiont of the aphid Acyrthosiphon pisum (49 % similarity, 33 % identity; van der Wilk et al, 1999), and Salmonella typhimurium phage P22 (55 % similarity, 37 % identity; . The lysozymes from HP1, P1 (protein gp17), P22 (gp19) and APSE-1 (endolysin P13) share structurally conserved regions marked in the alignment with ORF178 (Fig.…”
Section: Sequence Analysis Of Orf178 and Orf119mentioning
confidence: 99%
“…APSEs are temperate bacteriophages related to the lambdoid phage P22 (Podoviridae) [7,11]. There are two APSE variants (APSE-2 and APSE-3) commonly found in North American populations of A. pisum.…”
Section: Introductionmentioning
confidence: 99%